PENGARUH CORPORATE GOVERNANCE, STRUKTUR KEPEMILIKAN DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Rudiyanto, Rudiyanto; Fatimah, Imas (The Asia Pacific Journal Of Management Studies, 2023)
Earnings management practices occur in all countries, but the highest levels occur in countries with weaker legal institutions. This research aims to empirically test the influence of corporate governance, ownership structure and company size on earnings management in the non-cyclical consumer sector. Our research uses secondary data taken via the website https://www.idx.co.id with the research object being Consumer Non-Cyclical sector companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. Based on the data that has been collected and the tests that have been carried out on these problems, it can be concluded that the board of commissioners, independent commissioners and audit committees do not have a significant influence on earnings management. We found that two dimensions of ownership structure have a negative effect on earnings management in non-cyclical consumer companies listed on the Indonesia Stock Exchange during the 2018-2022 period. Meanwhile, company size has a significant positive effect on earnings management practices. Managerial ownership and institutional ownership have an asymmetric relationship with earnings management. Meanwhile, on the other hand, company size and earnings management are related symmetrically.